PENANGGULANGAN TINDAK PIDANA PERDAGANGAN ORANG MELALUI MEDIA SOSIAL DALAM PERSPEKTIF KRIMINOLOGI - Hendryani; Abdurrakhman Alhakim; Tantimin (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Handling human trafficking has its own regulations, this research aims to use social media as a role in handling human trafficking by using normative legal research methods with primary and secondary data sources and by data analysis using qualitative descriptive data, the researcher conducted research on handling the crime. The criminal act of trafficking in persons through social media from a criminological perspective, where the discussion will be discussed further regarding the regulations related to overcoming the criminal act of trafficking in persons through social media from a criminological perspective as well as overcoming the criminal act of trafficking in persons through social media from a criminological perspective. Agencies and institutions have given them the right to disseminate and leave digital traces to assist the investigation process. Apart from violating the human trafficking law, human trafficking also violates the human rights law because by carrying out human trafficking, human trafficking eliminates a person’s rights as stated in the human rights law. Criminology is divided into three aspects, namely crimes against person, crimes against property, crimes against public decency. Cases of criminal acts of human trafficking that are publicly disclosed regarding the mode and conditions of the perpetrators and victims are known to connected the three aspects of criminology.